2019
DOI: 10.1038/s41598-019-45311-y
|View full text |Cite|
|
Sign up to set email alerts
|

Bidirectional regulatory potentials of short-chain fatty acids and their G-protein-coupled receptors in autoimmune neuroinflammation

Abstract: Microbial metabolites, produced in the intestine, have significant effects on inflammatory diseases throughout the body. Short-chain fatty acids (SCFAs) have protective effects on experimental autoimmune encephalitis (EAE) responses but the detailed roles of SCFAs and their receptors in regulating autoimmune CNS inflammation have been unclear. SCFAs metabolically regulate T cells and change the phenotype of antigen presenting cells to efficiently induce IL-10 + regulatory T cells. In lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
127
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(141 citation statements)
references
References 58 publications
6
127
1
Order By: Relevance
“…The Treg frequency directly correlated with fecal SCFA concentrations. Similar ndings were made in an US cohort: patients suffering from a secondary progressive MS (SPMS) showed SCFA blood concentrations which were 50-65% reduced in comparison to healthy controls (19).…”
Section: Introductionsupporting
confidence: 69%
“…The Treg frequency directly correlated with fecal SCFA concentrations. Similar ndings were made in an US cohort: patients suffering from a secondary progressive MS (SPMS) showed SCFA blood concentrations which were 50-65% reduced in comparison to healthy controls (19).…”
Section: Introductionsupporting
confidence: 69%
“…It is proposed, that in normal and pathological conditions PPA and butyrate increase neuronal histone acetylation, but are metabolized mainly in glia (Nguyen et al, ). Glial effects may be related to the presence of free fatty acid receptors on brain macro‐ and microglia (Erny, Hrabe de Angelis, & Prinz, ; Park, Wang, Wu, Mao‐Draayer, & Kim, ). Our EM studies revealed that the rapid activation of glia has developed even after a single injection of a relatively low dose of PPA (Lobzhanidze et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…While it is possible that SCFA levels may directly impact immunological pathways not assessed in this study, the lack of clear association between SCFA production and in ammation likely evinces the complexity of the relationship between these physiological processes. Both pro-and anti-in ammatory activities of SCFAs have been documented (44,45), and dietary supplementation of SCFAs produces variable effects on in ammation which appear to be strongly in uenced by the range of SCFA concentrations involved (46). Further investigation of the effects of SCFAs on immune responses in the gut, the blood, and the central nervous system in the context of PD pathology is needed.…”
Section: Discussionmentioning
confidence: 99%